FORMATION OF WEAR AND HARDRESISTANT COATINGS Ni-Al-Ti-C-SiO2-Al2O3-B2O SYSTEMS - Харченко, Сергій (Problems of Friction and Wear, 2022)
The laws of formation of wear and hardresistant coatings of the Ni-Al-Ti-C-SiO2-Al2O3-B2O system are shown in the work and the results of their research at friction loading are given. The proposed coatings are characterized by having an order of magnitude higher resistance to oxidation compared to traditional heatresistant coatings, with high wear resistance. In the whole range of tests, the indicators of wear intensity remain virtually unchanged, and much lower than traditionally used wear-resistant materials. At change of speed of sliding in the conditions of the increased loadings and temperatures intensity of wear remains practically invariable and is twice less in comparison with coverings of tungsten carbide.